2015
DOI: 10.1186/s12993-015-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of kynurenines in adult patients with attention-deficit hyperactivity disorder (ADHD): a case–control study

Abstract: BackgroundThe essential amino acid tryptophan is catabolised mainly through the kynurenine pathway. Altered circulating levels of kynurenines have been reported in chronic inflammatory conditions and in several neuropsychiatric disorders, including depression and schizophrenia. Candidate gene studies suggest that genes related to the kynurenine catabolism may be associated with attention-deficit hyperactivity disorder (ADHD). Additionally, ADHD patients often report comorbid depression or anxiety. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 45 publications
2
51
0
1
Order By: Relevance
“…Studies have shown that tryptophan metabolites modulate several neurotransmitter systems, including dopaminergic transmission. Of note, lower levels of tryptophan and tryptophan metabolites are associated with the severity of ADHD symptoms ( 30 ). Pro-inflammatory cytokines can also activate microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tryptophan metabolites modulate several neurotransmitter systems, including dopaminergic transmission. Of note, lower levels of tryptophan and tryptophan metabolites are associated with the severity of ADHD symptoms ( 30 ). Pro-inflammatory cytokines can also activate microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of this pathway, resulting in hyper- or hypofunction of active metabolites, is associated with neurodegeneration and other disorders, such as depression and schizophrenia [51], diabetes mellitus [52,53], attention-deficit hyperactivity disorder [54], and cataract [13]. Some KP metabolites are neuroactive, while others are molecules with prooxidant and antioxidant properties [3].…”
Section: Discussionmentioning
confidence: 99%
“…VDR deficiency could enhance kynurenine metabolite levels, which may be implicated in ADHD pathology, yet the results are inconclusive. A Norwegian study compared serum levels of kynurenines in 133 adult ADHD patients versus adult controls (18–40 years) and found the ADHD group did not have lower levels of tryptophan, kynurenic acid or xanthurenic acid [ 141 ]. These findings contradict a Roman study testing serum kynurenine metabolite in ADHD children ( n = 102), who exhibited increased kynurenine (+48.6%) and reduced serum KA (−11.2%) and XA levels (−12.5%) compared with healthy controls ( n = 62) [ 142 ].…”
Section: Microbial Metabolite In Autism Spectrum Disorder and Attentimentioning
confidence: 99%